Determinants of foreign customer’s satisfaction towards Alam Hidro (M) Sdn Bhd Services / Syazwani Zainudin - Zainudin, Syazwani (2011)
Alam Hidro (M) Sdn Bhd (AHSB) is a company which provides services to the customer either from foreign or domestic country. It provides services to the customer in terms of construction and installation, underwater engineering and inspection services and others. This project paper is done to determine the level of foreign customer satisfaction towards AHSB services, to identify the drivers that influence foreign customer satisfaction towards AHSB services and to provide recommendation on how to deliver better services in order to increase foreign customer retention rate. This study used descriptive data. Based on the result and findings majority of the respondents are agree with the quality of service, counter of customers’ complaint, call centre and physical facilities contribute to the foreign customer satisfaction because the respondents are the foreign customer itself. However, the staff still needs a training and workshop to maintain their foreign customers’ satisfaction. Other than that, the result and findings for pricing of AHSB services show that most of the customers are disagree with the pricing of AHSB services because the customers’ perceived that the price are not competitive. In order to solve the price problem, the company should offer competitive price and at the same time retain the quality of service and product offered, definitely the customers would be loyal to the company.